Innovation, Sustainability, Development and Social Inclusion: Lessons from Latin America - Arond, Elisa (2011)
The paper briefly describes the heterogeneous context and history of the Latin American region with specific attention to STI policies and institutions, as well as the particular challenge of effectively linking STI to social needs. It highlights the important historic contribution of the Latin American School on Science, Technology and Development, and the relevance and synergies of ideas presented by these and contemporary Latin American researchers in relation to the New Manifesto’s ‘3Ds’. The paper documents some examples – from public, private and civil society spheres – of current Latin American initiatives that illustrate regional efforts to develop, in different ways, a 3D innovation agenda, as well as constructing and putting into practice the different New Manifesto ‘Areas for Action’. It also questions the relative weight of these efforts compared to conventional priorities of competitiveness and growth, and highlights some of the obstacles to realising 3D aims. In particular, it underscores persistent social and economic inequalities, issues of institutional and political resistance to change, and the role of power relations (at multiple levels) in determining directions of science, technology, and innovation, and STI policy, as topics worth exploring further in the future.